2020
DOI: 10.1016/j.heliyon.2020.e05336
|View full text |Cite
|
Sign up to set email alerts
|

Visual contrast sensitivity could be an early marker of diabetic retinopathy

Abstract: The present study aimed to explore the early predictive marker of diabetic retinopathy (DR) and to elucidate the associated demographic, metabolic, and ocular factors. We enrolled 43 type 2 diabetic subjects with mild non-proliferative retinopathy (MNPDR), 30 diabetic subjects with no retinopathy (DNR), and 35 healthy controls (HC). The study groups showed no significant alteration in central macular thickness (CMT) and visual acuity (VA). The contrast sensitivity (CS) score was found to be significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…Increased levels of TC, LDL-C, TG, MDA, and VEGF among NPDR subjects compared to DNR are in agreement with similar studies conducted earlier. 65 , 66 However, significant negative correlations of those conventional lipid parameters, MDA, an indicator of oxidative stress, 63 and VEGF with levels of miRs in our study could be due to up-regulation of target genes of miR-126 and miR-132 in NPDR. For example, the voltage-dependent anion-selective channel protein 2 ( VDAC2 ) and low-density lipoprotein receptor ( LDLR ), validated targets of miR-132 are associated with cholesterol metabolism pathway (KEGG ID: hsa04979 ).…”
Section: Discussioncontrasting
confidence: 55%
“…Increased levels of TC, LDL-C, TG, MDA, and VEGF among NPDR subjects compared to DNR are in agreement with similar studies conducted earlier. 65 , 66 However, significant negative correlations of those conventional lipid parameters, MDA, an indicator of oxidative stress, 63 and VEGF with levels of miRs in our study could be due to up-regulation of target genes of miR-126 and miR-132 in NPDR. For example, the voltage-dependent anion-selective channel protein 2 ( VDAC2 ) and low-density lipoprotein receptor ( LDLR ), validated targets of miR-132 are associated with cholesterol metabolism pathway (KEGG ID: hsa04979 ).…”
Section: Discussioncontrasting
confidence: 55%
“…In the present study, plasma conventional lipid components of diabetic subjects like TCH, LDL-C showed a tendency of gradually increasing towards the pathogenesis of DR, and TG was found to be increased towards pathogenesis with the severity of DR. The findings are partially supported by Cowdhuri et al, 2017 and Pramanik et al, 2020 who have demonstrated a significant increment of TCH, LDL-C, and TG levels in MNPDR compared to HC and DNR [ 1 , 22 ]. Another prospective study by Prajapati et al, 2017 showed a stepwise increment of TCH, LDL-C, and TG from NPDR to PDR [ 35 ].…”
Section: Discussionmentioning
confidence: 53%
“…Blood level of HbA1C, plasma glucose (fasting and postprandial), and conventional lipid profile components were measured using commercial kits by standard manufacturer instructed protocols as discussed in our previous paper [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the different detrimental pathways regarding enhanced glycation, oxidative stress, and lipid peroxidation derived from chronic hyperglycemia, cells attempt to create a barrier or defense system to maintain normal physiology. Superoxide dismutase (SOD), glutathione reductase (GR), glutathione peroxidase (GPX), and reduced glutathione (GSH), which are the normal cellular protectors against the development of damaging toxicity of free radicals and lipid peroxides, are severely affected by advanced AGEs, MDA, and ROS [ 3 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%